2017
DOI: 10.1556/030.65.2018.001
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of Staphylococcus aureus nasal carriage among children in Szolnok, Hungary

Abstract: We collected nasal samples from 1,390 healthy 3-7 years old children in Szolnok city, Hungary, in 2012. We detected 476 Staphylococcus aureus isolates from 474 children. In two occasions, two different S. aureus were isolated, based on hemolysis type and pulsed-field gel electrophoresis pattern. S. aureus carriage rate was calculated to be 34.1% similar to others studies. Male gender was found to be a risk factor for carriage by statistical analysis. Altogether, four methicillin-resistant S. aureus (MRSA) stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
7
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 23 publications
6
7
1
1
Order By: Relevance
“…This prospective cohort study identified risk factors for MDR S. aureus carriage in newborn infants and assessed the risk of MDR S. aureus vaginal carriage of mothers for MDR S. aureus carriage in their newborn infants. The gender of the newborn infants was not associated with MDR S. aureus isolates in this study, which was different to previous studies (22, 23). The mechanism between gender and MDR S. aureus carriage requires further exploration.…”
Section: Discussioncontrasting
confidence: 99%
“…This prospective cohort study identified risk factors for MDR S. aureus carriage in newborn infants and assessed the risk of MDR S. aureus vaginal carriage of mothers for MDR S. aureus carriage in their newborn infants. The gender of the newborn infants was not associated with MDR S. aureus isolates in this study, which was different to previous studies (22, 23). The mechanism between gender and MDR S. aureus carriage requires further exploration.…”
Section: Discussioncontrasting
confidence: 99%
“…Older children and young adults, as well as males, are known to be more frequently colonized by S. aureus. 9,[12][13][14][15] As we have observed, other authors have also reported higher colonization rates in urban settings in asymptomatic children or among adults with SSTIs. 16,17 In our study, patients with chronic conditions presented higher rates of colonization, although most of them were atopic children.…”
Section: Discussionsupporting
confidence: 84%
“…Recent studies performed in different regions of Europe have also reported high S. aureus colonization rates in children (34% to 53%). 13,32 These data suggest that S. aureus colonization could be increasing in children in our continent. In addition, although the isolation of MRSA was low in our cohort (1.4%), it is substantially higher than the rates reported by several authors in European children and even in adults (0.14-0.8%) 9,13,26,32 which is a concerning issue.…”
Section: Discussionmentioning
confidence: 75%
“…According to the MLST database, members of ST45 were previously isolated from human carriers in Germany, Philippines and from an asymptomatic dog in the USA [28]. ST45 was also identified earlier in our carriage studies (represented by both MRSAs and MSSAs), from children and adults [62,63], veterinarians and dogs [unpublished], so it seems to be a common carried type in Hungary, being present for a long time. This assumption is further supported by the fact that Q47 and Q85 were isolated from two different geographical areas in Hungary.…”
Section: Plos Onesupporting
confidence: 56%